NF-κB Activation by Double-Stranded-RNA-Activated Protein Kinase (PKR) Is Mediated through NF-κB-Inducing Kinase and IκB Kinase - Zamanian-Daryoush, Maryam (American Society for Microbiology, 2000)
The interferon (IFN)-inducible double-stranded-RNA (dsRNA)-activated serine-threonine protein kinase (PKR) is a major mediator of the antiviral and antiproliferative activities of IFNs. PKR has been implicated in different stress-induced signaling pathways including dsRNA signaling to nuclear factor kappa B (NF-κB). The mechanism by which PKR mediates activation of NF-κB is unknown. Here we show that in response to poly(rI) · poly(rC) (pIC), PKR activates IκB kinase (IKK), leading to the degradation of the inhibitors IκBα and IκBβ and the concomitant release of NF-κB. The results of kinetic studies revealed that pIC induced a slow and prolonged activation of IKK, which was preceded by PKR activation. In PKR null cell lines, pIC failed to stimulate IKK activity compared to cells from an isogenic background wild type for PKR in accord with the inability of PKR null cells to induce NF-κB in response to pIC. Moreover, PKR was required to establish a sustained response to tumor necrosis factor alpha (TNF-α) and to potentiate activation of NF-κB by cotreatment with TNF-α and IFN-γ. By coimmunoprecipitation, PKR was shown to be physically associated with the IKK complex. Transient expression of a dominant negative mutant of IKKβ or the NF-κB-inducing kinase (NIK) inhibited pIC-induced gene expression from an NF-κB-dependent reporter construct. Taken together, these results demonstrate that PKR-dependent dsRNA induction of NF-κB is mediated by NIK and IKK activation.